1996
DOI: 10.1097/00006534-199610000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TGF-β on Keloid Fibroblast Proliferation and Collagen Synthesis

Abstract: Keloids are characterized by an overabundant deposition of collagen, and they recur frequently following excision. Fibroblasts isolated from keloid tissue and maintained in cell culture continue to express an increased capacity to produce collagen. In an effort to define the mechanisms responsible for keloid formation, the potential of exogenous transforming growth factor beta 1 (TGF-beta 1) to differentially affect DNA synthesis and collagen expression in cultured human fibroblasts derived from keloid or norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
206
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(217 citation statements)
references
References 16 publications
10
206
0
1
Order By: Relevance
“…Bettinger et al also found a significant increase in the response rate to TGF-ß in KFs, with an increase in fibroblast proliferation and collagen synthesis (15). Increased rates of proliferation and collagen synthesis suggest an altered response of KFs to this cytokine, which might reflect a modification in the regulatory pathway that occurs at the receptor level or during intracellular transduction (4,9).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bettinger et al also found a significant increase in the response rate to TGF-ß in KFs, with an increase in fibroblast proliferation and collagen synthesis (15). Increased rates of proliferation and collagen synthesis suggest an altered response of KFs to this cytokine, which might reflect a modification in the regulatory pathway that occurs at the receptor level or during intracellular transduction (4,9).…”
Section: Discussionmentioning
confidence: 95%
“…Treatment with TGF-ß1 results in an increase in fibronectin biosynthesis leading to an overproduction of ECM components in keloid fibroblasts (3,9). In addition, TGF-ß1 treatment upregulates collagen production, and keloid fibroblasts show a greater proliferative capacity than normal human dermal fibroblasts (3,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Modifications in growth factor-regulated cell growth and apoptosis, intracellular signal transduction, and epidermis-dermis interactions have been reported. [13][14][15][16][17][18][19][20][21] Changes in the level of genes involved in the above phenomena were also detected in gene profiling studies. 22,23 Despite these findings, knowledge-based specific approaches for prevention and efficacious treatment of keloids are still absent, and the lack of proper in vitro and animal models that recapitulate the pathophysiology of keloids further hampers progress.…”
mentioning
confidence: 99%
“…As for PEAK PlasmaBlade versus conventional surgery, one study showed significant reduction in thermal injury and improved wound strength and histology with better visual assesment of scars 6 . It has been shown that PEAK PlasmaBlade reduces level of inflammation, thus leading to good epithelization resulting in improved healing and cosmesis [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%